P1-025Nivolumab for poor performance status patients : retrospective analysis. (7th October 2019) - Matsumoto, Toshihiko; Kimura, Shogo; Himei, Hitomi; Okazaki, Ukyo; Kurioka, Yusuke; Tsuduki, Takao; Takagi, Shijiro; Takatani, Masahiro; Watanabe, Takanori; Morishita, Hirofumi
Abstract: Objective: Nivolumab has changed the treatment of advanced gastric cancer (AGC). Nivolumab shows better outcome compared to best supportive care in AGC patients who received at least two prior regimen. Although there is not reliable date of poor performance status(PS) AGC patients who received nivolumab.We investigated efficacy and safety of nivolumab for AGC patients with poor PS. Methods: We retrospectively collected clinicopathologic data from patients with AGC who received nivolumab monotherapy in our institution from October 2017 to January 2019. Results: 37 AGC patients received nivolumab in Himeji Red Cross hospital from October 2017 to January 2019.We analyzed 17 patients who were PS over 1. 15 patients was male, median age was 64 (42-80), 10 patients was PS 2 and 7 patients PS 3, 11 patients were diffuse type, median number of metastatic organ was 2(range 1-5), 3 patients had liver metastasis, 13 patients had peritoneum dissemination and ascites.12 patients received 2 prior regimen, 5 patients received over 2 regimen. Median progression free survival was 29 days(95% CI: 21-65 days) and overall survival was 85 days(95% CI: 35-111 days), response rate was 6%, disease control rate was 19%, and 6 months survival rate was 12%. Immune-related adverse events(iRAEs) were observed 4 patients(24%), colitis was observed 2patients(12%), hypothyroidism was observed 2patients(12%), and liver dysfunction was observed 1 patient(6%). Severe iRAEs was only one patients(colitis). Conclusion: This study suggested that nivolumab has a modest effect and is feasible as third line or later line for AGC patients.